A Novel Combination Cancer Therapy with Iron Chelator Targeting Cancer Stem Cells via Suppressing Stemness - Katsura, Yuki (Cancers (Basel), 2019)
Excess iron causes cancer and is thought to be related to carcinogenesis and cancer progression including stemness, but the details remain unclear. Here, we hypothesized that stemness in cancer is related to iron metabolism and that regulating iron metabolism in cancer stem cells (CSCs) may be a novel therapy. In this study, we used murine induced pluripotent stem cells that expressed specific stem cell genes such as Nanog, Oct3/4, Sox2, Klf4, and c-Myc, and two human cancer cell lines with similar stem cell gene expression. Deferasirox, an orally available iron chelator, suppressed expression of stemness markers and spherogenesis of cells with high stemness status in vitro. Combination therapy had a marked antitumor effect compared with deferasirox or cisplatin alone. Iron metabolism appears important for maintenance of stemness in CSCs. An iron chelator combined with chemotherapy may be a novel approach via suppressing stemness for CSC targeted therapy.